Cross-Sectional Associations between Playing Sports or Electronic Games in Leisure Time and Life Satisfaction in 12-Year-Old Children from the European Union - Diego Gomez-Baya; Hugo Sarmento; Javier Augusto Nicoletti; Francisco Jose Garcia-Moro (MDPI AG, 2022)
Leisure time activities in childhood may have a crucial role in the development of subjective well-being. Nevertheless, more research is needed with cross-national samples concerning the differential effects of lifestyles on life satisfaction. The aim of this cross-sectional study was to analyze the associations between the frequency of playing sports/exercise or playing electronic games on life satisfaction in a sample of 12-year-old children from nine countries from the European Union. The data used in this publication come from the third wave of the Children's Worlds project, an international survey of children's lives and well-being whose administration started in 2017. The sample was composed of 10,626 children (50.9% boys) from Estonia, Belgium, Croatia, Hungary, Italy, Malta, Poland, Romania, and Spain. They completed the Student Life Satisfaction Scale and answered two questions to assess the frequency of playing sport or exercise, and the frequency of playing electronic games. The results indicated notable scores in life satisfaction in all participating countries. The results showed some differences between boys and girls, and among the countries, in the frequency of sport practice and electronic games in the leisure time, as well as in the overall level of life satisfaction. The results also underlined that sport practice had a greater positive effect on life satisfaction than the use of electronic games. Thus, this study highlights the need to design programs to promote sport practice in leisure time for 12-year-old children in Europe, in order to protect their subjective well-being.